2022
DOI: 10.4102/sajcd.v69i1.840
|View full text |Cite
|
Sign up to set email alerts
|

Newborn and infant hearing screening at primary healthcare clinics in South Africa designated as National Health Insurance pilot sites: An exploratory study

Abstract: Primary healthcare is the first level of care and entry for individuals into the healthcare system, which is accessible at PHC clinics and community health centres (CHCs). The services at these healthcare facilities include maternal and child care, immunisations, family planning and care for chronic illnesses, usually managed by nurses with advisory support and regular visits by medical practitioners and other relevant healthcare specialists (Bresick, Von Pressentin, & Mash, 2019;Cullinan, 2006). Such services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Hospitals depend on the availability of resources such as screening and diagnostic audiological equipment, human resources in the form of audiologists, finances and clinical protocols to provide EHDI services. 14 Thus, a lack of any of these resources can impede the provision of EHDI. Findings from this study showed an uneven distribution of the essential resources for providing EHDI within the state hospitals in the EC Province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitals depend on the availability of resources such as screening and diagnostic audiological equipment, human resources in the form of audiologists, finances and clinical protocols to provide EHDI services. 14 Thus, a lack of any of these resources can impede the provision of EHDI. Findings from this study showed an uneven distribution of the essential resources for providing EHDI within the state hospitals in the EC Province.…”
Section: Discussionmentioning
confidence: 99%
“…While EHDI has proven long-term savings globally, as the early rehabilitation of paediatric HL prevents the development of the negative impact of HL, previous research has reported the lack of resources to provide EHDI in various provinces in South Africa. 10 , 11 , 12 , 13 , 14 However, there is a paucity of the literature on the availability of resources to provide EHDI at state facilities in the Eastern Cape (EC) province. This lack of context-specific literature may negatively influence budget allocations for the provision of EHDI at state facilities, including employment of qualified clinical staff to provide quality healthcare, procurement of equipment for assessment and diagnosis of HL and procurement of assistive devices for HL rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…While the current guidelines provide for biochemical NBS, the implementation thereof and adherence to previous guidelines have been limited, and to date, no progress reports have been issued [56][57][58][59][60][61] .…”
Section: History Of Biochemical Nbs In Samentioning
confidence: 99%